Manajemen Pengembangan Sarana dan Prasarana Dalam Implementasi Manajemen Berbasis Sekolah: di Ma Al-Mubarok Lampung Tengah - Lukman Abdul Majid (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2021)
In relation to the implementation of facilities and infrastructure, the availability of facilities and infrastructure is one of the important components that must be met in supporting the education system. Management of educational facilities and infrastructure can be defined as the entire process of procurement and utilization of components that directly or indirectly support the educational process to achieve educational goals effectively and efficiently. School-based management (SBM), is an approach to improving the quality of education through the granting of authority to schools to manage school resources in accordance with the conditions and demands of the school environment. SBM gives schools greater authority to manage their own schools. Schools are seen as more aware of their own strengths, weaknesses, threats, opportunities and needs, so that the management of school resources will be more effective and efficient at the school level. This study concludes that the implementation of infrastructure management at MA Al-Mubarok is always carried out optimally. This can be seen in the completeness of the infrastructure owned by MA Al-Mubarok in handling the infrastructure, which is directly handled by the respective field of study teachers under the supervision of the Deputy Head of Infrastructure. Al-Mubarok carried out sequentially, starting from planning procurement, procurement, maintenance, inventory and elimination. This process is carried out so that the infrastructure in the madrasa is always in a neat, orderly and orderly condition.